In search for political consciousness: The role of workers' education - Luciole Sauviat (International Labour Organization (ILO), 2015)
Unionists and labour activists often speak about workers' education, but what does the concept really imply and does it actually play a role for political consciousness? This paper is the synthesis of empirical studies from a Global Labour University (GLU) alumni research group on Workers' Education. Its uniqueness are case studies, where workers' education has been very seldom studied. Just to mention a few of the nine in depth field studies: shop steward training in Malawi, labour rights workshops in Indonesia, party education in a train depot in China, organising workshops in a syndicalist union in Canada. Workers' education is a contested educational concept and its definition, aims and methods through history are summarized to help to analyse the kind of education presented in the case studies. The paper also highlights Freire and Gramsci theories on political consciousness and education since they are the two authors who were convinced that workers' education can contribute to see oneself as the subject of history and that it therefore has an impact on political practices. The central part of the paper deals with the different case studies and discusses their findings along the following questions: What is the definition, aim and format of the educational activities presented in the case studies? Can we assess any impact of these activities on the political consciousness of the participants? The challenge to assess something as fluid as consciousness is addressed with criteria categorised in three forms of political consciousness: one labelled as "counter-hegemony to capitalism", a second as "class consciousness" and the third as "eing generally politically active" The case study authors have interviewed workers on their political practices after the education activities they have participated in and classified their findings along these three forms of political consciousness. In many cases a gap between knowledge and practices is noticeable. In a union environment, it is the so called class consciousness that is at best developed. Noteworthy, the studies show that workers themselves asses what they have learnt and why they can't or can practice it.
Keywords: 330; workers education; tade union role; politics; social structure; case study